Impact of water quality on pesticides and fertilizer compatibility (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Mixtures of two or more pesticides are very common in contemporary agriculture. However, changes in their efficacy or biological activity, such as synergism and antagonism, phytotoxicity, persistence, toxicity to non-target organisms, may occur as a consequence. This study was conducted in order to evaluate the compatibility of insecticides (cyantraniliprole – Exirel, chlorantraniliprole – Coragen 20 SC), a fungicide (captan – Merpan 50 WP) and a foliar fertilizer (Folia Stim Mix TE), as well their mixtures, in spray liquids, depending on water quality (well water from two locations in Serbia – Mala Remeta and Čerević). These products are used to control the most significant peach pests, and as an additional source of nutrients. Wateranalysis (pH, hardness, electroconductivity, chloride, nitrate, nitrite, ammonia, calcium and iron content) and tests of physico-chemical properties of the spray liquids (pH, suspensibility, dispersibility, surface tension, and electroconductivity) were performed in a laboratory experiment according to standard methods. The physico-chemical properties of the liquids changed depending on water quality and components incorporated in the mixture. However, all tested spray liquids showed consistency and compatibility over a period of 24 hours.
Keywords: pesticides, fertilizer, mixture, water quality, physico-chemical properties, compatibility